Effect of the composition on the thermal behaviour of the SrSn1-xTixO3 precursor prepared by the polymeric precursor method - de Oliveira, A. L M; Silva, M. R S; Sales, H.; Longo, Elson [UNESP]; Maia, A. S.; Souza, A. G.; Santos, I. M G (Springer Nature, 2013)
Strontium stannate titanate Sr(Sn, Ti)O3 is a solid solution between strontium stannate (SrSnO3) and strontium titanate (SrTiO3). In the present study, it was synthesized at low temperature by the polymeric precursor method, derived from the Pechini process. The powders were calcined in oxygen atmosphere in order to eliminate organic matter and to decrease the amount of SrCO3 formed during the synthesis. The powders were annealed at different temperatures to crystallize the samples into perovskites-type structures. All the compositions were studied by thermogravimetry (TG) and differential thermal analysis (DTA), infrared spectroscopy (IR) and X-ray diffraction (XRD). The lattice former, Ti4+ and Sn4+, had a meaningful influence in the mass loss, without changing the profile of the TG curves. On the other hand, DTA curves were strongly modified with the Ti4+:Sn4+ proportion in the system indicating that intermediate compounds may be formed during the synthesis being eliminated at different temperature ranges, while SrCO3 elimination occurs at higher temperature as shown by XRD and IR spectra. © 2013 Akadémiai Kiadó, Budapest, Hungary.
Keywords: Crystallization and thermal analysis; Perovskite; Strontium stannate titanate